Gaya Bahasa IstifhÃ¢m: Kajian Fungsi Retorik - Mardjoko Idris (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2020)
The Qur'an is a medium of interaction between Allah and His servants. In interacting, the Qur'an uses a variety of sentences, including interrogative sentences (istifhÃ¢m). An interrogative sentence is a sentence used if the speaker wants to ask the opponent something. The sentence of IstifhÃ¢m in the sense of Science Balaghah is to demand the understanding of something from the adversary, the claim comes from the higher to the lower, using one of the eight pirati istifhÃ¢m. The istifhÃ¢m tool is Ø§Ù„Ù‡Ù…Ø²Ø© (whether); Ù‡Ù„ (whether); Ù…Ù† (anyone);Ù…Ø§ (what); ÙƒÙŠÙ (how); ÙƒÙ… (how much); Ø£ÙŠÙ† (where); Ø£ÙŠØ§Ù† (when); Ù…ØªÙ‰ (when); Ø£Ù†Ù‰ (when); Ø£Ù‰ (which). In pragmatic studies, interrogative sentences in addition to being functioned as the original meaning of a question, are also widely functioned for other purposes in accordance with the context that became the background of the birth of a speech. Interrogative sentences in the Qur'an are functioned for command (amr), prohibition (nahyun), equating (taswiyah), negate (nafyun), rejection (inkÃ¢r), longing (tasywÃ®q), decree (taqrÃ®r), consider far (istib'Ã¢d), glorify And allah is all-forgiving, all-merciful.